Search for production of single top quarks via tcg and tug flavor-changing-neutral-current couplings - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Amer Physical Soc, 2007)
We search for the production of single top quarks via flavor-changing-neutral-current couplings of a gluon to the top quark and a charm (c) or up (u) quark. We analyze 230 pb(-1) of lepton+jets data from p (p) over tilde collisions at a center of mass energy of 1.96 TeV collected by the D0 detector at the Fermilab Tevatron Collider. We observe no significant deviation from standard model predictions, and hence set upper limits on the anomalous coupling parameters kappa(c)(g)/Lambda and kappa(u)(g)/Lambda, where kappa(g) define the strength of tcg and tug couplings, and Lambda defines the scale of new physics. The limits at 95% C.L. are kappa(c)(g)/Lambda < 0.15 TeV-1 and kappa(u)(g)/Lambda < 0.037 TeV-1.